Design of PLC Electrical Control System - Ye, Likai (Journal of Theory and Practice of Engineering Science, 2024)
With the continuous expansion and development of factory enterprise scale, the development of automatic batching control system has also been accelerated. Batching mixing control system is a kind of raw materials mixed together according to a certain proportion, processing to produce a certain product process. This paper mainly designs and realizes the batching mixing control system of programmable logic controller (PLC). By precisely controlling the proportion of batching and the mixing time, the system is widely used in chemical, pharmaceutical, food and other fields to improve production efficiency and product quality. PLC system is a flexible, programmable electrical control equipment, because of its powerful, easy to use, high reliability characteristics, often used as the field data acquisition and equipment control. This paper mainly introduces the automatic control of liquid mixing system by Siemens PLC. The control object, hardware composition, software design and system function of the PLC based mixing, automatic mixing and automatic discharging system for two kinds of ingredients can simulate and display the whole working process of the liquid mixing system. The hardware of the system is mainly composed of S7-300 programmable controller, keys, stirring motor, frequency converter, solenoid valve and pump, etc. The programming software adopts Siemens programming software STEP7. The system transmits the collected field data to PLC through the weighing sensor, and after the PLC processes the field data logically, the corresponding control command is issued to complete the automatic control of the system. Finally, the system uses the communication interface to connect with the host computer to realize the communication between PLC and computer. The system has high degree of automation, strong flexibility, and can meet different production process requirements.